France : Financial Sector Assessment Program-Detailed Assessment of Observance of IOSCO Objectives and Principles of Securities Regulation. (IMF Staff Country Reports; Country Report ;, 2013)
This paper discusses key findings of the Detailed Assessment of Observance of International Organization of Securities Commissions (IOSCO) Objectives and Principles of Securities Regulation for France. The assessment reveals that France exhibits a high level of implementation of the IOSCO principles. The legal framework is robust and provides the Autorite de Marches Financiers (AMF) and the Autorite du Controle Prudentiel (ACP) with broad licensing, supervisory, investigative, and enforcement powers within their respective competences. There are robust arrangements for cooperation between the two authorities.